Granulomatous Interstitial Nephritis Presenting as Hypercalcemia and Nephrolithiasis - Saika Sharmeen; Esra Kalkan; Chunhui Yi; Steven D. Smith (Case Reports in Nephrology)
We report a case of acute kidney injury as the initial manifestation of sarcoidosis. A 55-year-old male was sent from his primary care physician’s office with incidental lab findings significant for hypercalcemia and acute kidney injury with past medical history significant for nephrolithiasis. Initial treatment with intravenous hydration did not improve his condition. The renal biopsy subsequently revealed granulomatous interstitial nephritis (GIN). Treatment with the appropriate dose of glucocorticoids improved both the hypercalcemia and renal function. Our case demonstrates that renal limited GIN due to sarcoidosis, although a rare entity, can cause severe acute kidney injury and progressive renal failure unless promptly diagnosed and treated.